2013
DOI: 10.1093/protein/gzt035
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cell surface proteins with bispecific antibodies

Abstract: Flow cytometry is an established method for fast and accurate quantitation of cellular protein levels and requires fluorescently labeled antibodies as well as calibration standards. A critical step for quantitation remains the production of suitable detection antibodies with a precisely defined ratio of antigen-binding sites to fluorophores. Problems often arise as a consequence of inefficient and unspecific labeling which can influence antibody properties. In addition, the number of incorporated fluorophores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In this work, we sought to generate optimal reagents for quantifying EGFR and c-MET cell-surface expression and evaluating the target engagement of a BsAb (JNJ-61186372) targeting these two receptors. Because the stoichiometry of Ab binding cannot be predicted and because the impact of valency and avidity on the accuracy of receptor quantitation measurements have been well documented ( 38 , 39 ), we chose to use a monovalent Ab system for quantitation. Additionally, understanding how a BsAb engages both its cell-surface targets can be challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we sought to generate optimal reagents for quantifying EGFR and c-MET cell-surface expression and evaluating the target engagement of a BsAb (JNJ-61186372) targeting these two receptors. Because the stoichiometry of Ab binding cannot be predicted and because the impact of valency and avidity on the accuracy of receptor quantitation measurements have been well documented ( 38 , 39 ), we chose to use a monovalent Ab system for quantitation. Additionally, understanding how a BsAb engages both its cell-surface targets can be challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Using different architectures of binders can affect the nature of interactions and thereby make systematic comparisons difficult to achieve. Because monovalent Abs lack avidity, the use of high affinity antigen-specific variants is essential ( 39 ). Equally important to our method is the application of labeling and purification methodologies that result in a 1:1 fluorochrome to protein (F/P) molar labeling ratio.…”
Section: Introductionmentioning
confidence: 99%
“…First, many tumor cells express high levels of specific receptors, including growth factor receptors (32), such that a few individual receptors occupy a substantial fraction of the total plasma membrane surface. For example, Chung et al recently showed that the bulky Her2 receptor (140 kDa) reaches a density of at least 1000 copies per square micrometer in Her2-positive breast cancer cells, covering $10% of the plasma membrane surface (33), which is similar to high membrane coverage by other receptor tyrosine kinases in tumor cells (34). The reduction in uptake rate due to saturation of endocytic structures by these receptors is thought to prolong receptor signaling at the plasma membrane surface, which, in combination with high levels of receptor expression, could promote tumor growth (32,35).…”
Section: Discussionmentioning
confidence: 99%
“…For such antibodies, an additional and thus error‐prone normalization step using beads which can bind a defined amount of antibody is required . Hapten‐binding antibodies circumvent these problems and in net effect reduce assay complexity, increase reproducibility and in its precision are at least as good as previously described methods . We have validated the method using different growth factor receptors (ErbB family and cMET) as cellular antigens.…”
Section: Bispecific Hapten‐binding Antibodies As Cell Biology Researcmentioning
confidence: 99%